SEMARANG RAGAM INSPIRASI DALAM MEMPERINGATI HARI ANAK NASIONAL KOTA SEMARANG 2020 (TALKSHOW, RAGAM LOMBA ANAK, PENTAS SENI DARING, WEBINAR, KONSER AMAL, DONASI) SEBAGAI MANAJER KREATIF DAN KOORDINATOR LOMBA - Laila Prativa Myranti; Adi Nugroho (Interaksi Online, 2021)
National Children's Day is the day the rights of Indonesian children are fulfilled, both for children residing in Indonesia and for children outside Indonesia. So that children in Indonesia get the same and broadest opportunity to be able to express themselves in positive activities. This year's National Children's Day will be held online, due to conditions that are currently experiencing the Covid-19 pandemic. Semarang City has also participated in celebrating National Children's Day by holding a series of activities in the form of talk shows, competitions, webinars, online art performances, charity concerts, and donation submissions. The theme of this event was "Being Great with the New Generation". We hoped that with the implementation of HAN 2020 the City of Semarang can provide education to children and parents about new cultures that must always be applied such as using masks, washing hands, behaving clean and healthy and can provide a forum for creativity and development for children while they have to stay at home. In a series of activities at the Semarang City 2020 National Children's Day Commemoration, the creative manager is responsible for all the creative outputs needed during the event, which in this case is related to design, documentation, and publication. In addition, the competition coordinator is responsible for arranging and ensuring that the competition can run smoothly and can still deliver the Semarang City National Children's Day 2020 theme campaign even though it is carried out with an online system. The commemoration of the National Children's Day for Semarang City 2020 which was held on July 13 to August 18 2020 managed to achieve the target of 432 competition participants, successfully held 6 talkshows and collaborated with local television and radio, the webinar reached the target of 555 participants, donations collected amounting to Rp. 14,954,250, online art performances attended by more than 500 participants and can bring influencers and speakers who are experts in their fields.